(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Some normal microorganisms of the macroorganism can, under certain conditions, cause subclinical and clinical manifestations of infectious diseases. Therefore, there is a growing need for a more detailed study of these microorganisms, the conditions that lead to the emergence of infectious diseases involving them, and the improvement of diagnostic, treatment, and prevention methods.